1985
DOI: 10.1159/000118729
|View full text |Cite
|
Sign up to set email alerts
|

The West Indian Manatee <i>(Trichechus manatus) </i>Lacks a Vomeronasal Organ

Abstract: Completely aquatic marine mammals of the order Cetacea such as whales and dolphins have a reduced or absent olfactory system and neither a vomeronasal organ nor an accessory olfactory bulb. In comparison, seals, which are only partially aquatic, have olfactory and accessory olfactory systems including the vomeronasal organ. Thus, there seems to be a strong relation between the degree of adaptation to an aquatic environment and the degree of reduction in olfactory structures. Sirenians, such as manatees and dug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
1

Year Published

1992
1992
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 21 publications
0
44
0
1
Order By: Relevance
“…Semiaquatic mammals, on the other hand, have variably maintained their olfactory receptor genes and olfactory structures (Kishida et al, 2007). For instance, while Trichechus manatus (West Indian manatee) displays evidence of a rudimentary olfactory system (Mackay-Sim et al, 1985), seals have a main olfactory bulb and an accessory olfactory bulb associated with a vomeronasal organ (Freitag et al, 1998). In the case of cetaceans, Kishida and Thewissen (2012) presented evidence suggesting that cetacean olfactory capabilities decreased gradually after adaptation to water, and some of these animals, like the baleen whales, still use olfaction to detect above-water odor plumes (e.g., Hagelin et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Semiaquatic mammals, on the other hand, have variably maintained their olfactory receptor genes and olfactory structures (Kishida et al, 2007). For instance, while Trichechus manatus (West Indian manatee) displays evidence of a rudimentary olfactory system (Mackay-Sim et al, 1985), seals have a main olfactory bulb and an accessory olfactory bulb associated with a vomeronasal organ (Freitag et al, 1998). In the case of cetaceans, Kishida and Thewissen (2012) presented evidence suggesting that cetacean olfactory capabilities decreased gradually after adaptation to water, and some of these animals, like the baleen whales, still use olfaction to detect above-water odor plumes (e.g., Hagelin et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, a recent study found that the female Australian sea lion (Neophoca cinerea) can identify the scents of its pups through naso-nasal contact, a behavior frequently observed in mother-pup interactions (Pitcher, Harcourt, Schaal, and Charrier, 2011). Mackay-Sim et al (1985) examined formalin-fixed tissue from the West Indian manatee (Trichechus manatus) and found that the nasal cavity lacked ducts necessary for the vomeronasal system. However, they observed main olfactory structures like olfactory cilia, olfactory epithelium, a perforated cribriform plate where nerve fibers from the olfactory nerve would presumably enter the central nervous system, and rudimentary olfactory bulbs, although they reported that some of these structures were poorly fixed and decomposed.…”
Section: Olfactory Systems or Lack Thereofmentioning
confidence: 99%
“…In all aquatic mammals, olfactory systems are reduced. In sirenians, the olfactory system is rudimentary and, similarly to odontocetes, they lack a vomeronasal organ (Mackay-Sim et al, 1985). In pinnipeds, presumably because they are semiaquatic, olfactory structures are small compared with terrestrial carnivores, but substantially well developed compared with sirenians and odontocetes.…”
Section: Reduction Of Olfaction and Reproportioning Of The Limbic Systemmentioning
confidence: 99%
“…In eutherian mammals, OR genes outnumber V1Rs several fold (for example, mice have 1037 functional OR genes and 187 functional V1R genes), however in the platypus V1R genes are more numerous [34] suggesting that vomeronasal function may be of greater significance than main olfactory function in this species. The vomeronasal system is completely absent in marine mammals [62], and so the presence of a complex VNO and large V1R gene family was somewhat surprising. In the platypus, the VNO does not connect to the nasal cavity but to the mouth, and when foraging underwater, the platypus seals its eyes, ears and nostrils, and uses its bill to detect prey.…”
Section: The Vomeronasal System In Mammalsmentioning
confidence: 99%